PEMENUHAN HAK ANAK DALAM PENERBITAN KARTU KELUARGA BAGI PASANGAN NIKAH SIRI PERSPEKTIF PERMENDAGRI NO. 9 TAHUN 2016 DAN MAQĀṢID ASY-SHARĪʻAH - Khoirur Roziqin, Moch.; Anwar, Khoirul (USRATUNA: Jurnal Hukum Keluarga Islam, 2023)
Children's rights are things that must be guaranteed by the State and their parents, as explained in Article 1 number 12 of Law no. 35 of 2014 concerning Amendments to Law no. 23 of 2002 concerning Child Protection, that children's rights are part of human rights that must be guaranteed, protected and fulfilled by parents, families, communities, the state, government and local governments. One of the government's roles in providing protection regarding children's rights, which has so far been constrained to make birth certificates, is through the policies of the minister of home affairs, including changing the rules by issuing Minister of Home Affairs Regulation (Permendagri) number 9 of 2016 related to accelerating the increase in coverage. birth certificates to protect and provide status for children whose origins are constrained. However, the government's role in providing protection regarding children's rights raises pros and cons in the community, some agree and some disagree. It is from here that the author is interested in studying the problem of fulfilling children's rights in issuing family cards for married couples from the Perspective of Permendagri No. 9 of 2016 and Maqāṣid Asy-Sharīʻah This type of thesis research is library research. The approach used in this research is normative juridical. In this study, the first data analysis used was descriptive-analytical, followed by a correlation process, and finally concluded. The results of this study indicate: First, Permendagri Number 09 of 2016 is an effort by the Government to increase the number of child birth certificate ownership in order to protect children's rights. Second, Pemendagri No. 9 of 2016 is in accordance with the values ​​of Maqāṣid Asy-Sharīʻah, namely ḥifzh al-dīn (Guarding children's rights and avoiding harassment of religion), ḥifzh al-nafs (Avoiding child exploitation cases), ḥifzh al-nasl (Avoiding any violence and discrimination against children), ḥifzh al-'aql (Avoiding child ignorance), ḥifzh al-māl (Avoiding neglect of children). Third, Pemendagri No. 9 of 2016 has a clear correlation with maqashid as-shariah values. namely prospering life on earth, maintaining order in it and always maintaining the stability of the benefit of nature. This can be seen in the Issuance of Family Cards for Siri Marriage Couples which is a new breakthrough / a solution to the legal vacuum in fulfilling children's rights.